Care at door-steps for persons with severe mental disorders: A pilot experience from Karnataka district mental health program. (March 2022) - Basavaraju, Vinay; Murugesan, Manisha; Kumar, Channaveerachari Naveen; Gowda, Guru S; Tamaraiselvan, Santhosh Kumar; Thirthalli, Jagadisha; Nagabhushana, Shashidhara Harihara; Manjunatha, Narayana; Bada Math, Suresh; Parthasarathy, Rajani; Arunachalam, Vikram; Kumar KS, Chetan; et al.
Background: Public funded outreach services for persons with severe mental disorders (SMDs), a norm in developed nations, is non-existent in India. We share our pilot experience with an indigenous model named 'Care at Doorsteps' (CADs) for persons with SMDs who dropped out from clinical care of District Mental Health Program (DMHP) at three sites of Karnataka, a south Indian state. Aim: The objectives of this study were to identify the reasons for drop outs from routine care and to assess the burden of illness and disability after the intervention. Methodology: Six-month prospective observational study on patients aged 18–60 years, diagnosed as Schizophrenia or bipolar disorder was conducted. Three home visits were made by the team and provided medications, also offered brief psychoeducation and counselling. Care-givers were interviewed to identify the reasons for drop outs and their expectations from the treating team. Patients were also assessed using the Clinical Global Impression Scale (CGI), Indian Disability Evaluation and Assessment Scale (IDEAS) and Burden Assessment Schedule (BAS) during each visit. Results: Ninety-six patients (50 males and 46 females) were followed up, of which 85 had a diagnosis of schizophrenia and 11 with bipolar illness. Common reasons for drop out were: single caregiver (breadwinner) unable to accompany the patient, loss of faith in medical treatment and financial constraints. Symptomatic improvement and restoration of productive work were the priority expectations. Over the course, the mean CGI-S showed significant reduction (4.81 ± 1.57, 4.46 ± 1.32 and 4.11 ± 1.39 respectively; p = 0.001). Mean score on BAS showed a significant reduction (85.76 ± 12.15, 83.46 ± 11.30, 84.27 ± 11.82; p = 0.04). Mean total IDEAS scores did not show significant change (13.27 ± 4.78, 12.82 ± 4.24, 13.17 ± 4.40; p = 0.16). Conclusion: Meaningful assertive outreach care is feasible in India and is found to be useful for persons with SMDs by utilising the already existing public sector resources.